Kurikulum ke arah penghasilan kemahiran berfikiran kritis, kreatif dan inovatif - Nordin, A.B. (Faculty of Education, University of Malaya, 2013)
Changing of world scenario as a result of destabilising of world economy as well as social, technological and even psychological and ethical phenomena, countries all over found themselves in need to review their education systems and in particular the curricula they had been pursuing all this while. Without exception Malaysia being engrossed with the ideal of becoming a high income industrialised nation finds herself in need to transform the system. The Prime Minister of Malaysia has decided that to transform the nation to achieve the sat ideal the education system has to breed man power of critical, creative, and innovative minds. Past education reforms had structurally brought about macro-level changes translated in the forms of increasing participation in education process and hence grossly increased the pool of talent potentials. As for micro-level changes particularly in the process of harnessing the pool available talent within the classroom the record has been quite dismal. Even with the introduction of Kurikulum Standard Sekolah Rendah to begin with, the focus of the transformation is still at the macro-level. If Malaysia is serious in wanting to produce out of the box thinkers then transformation must shift its focus by re-evaluating, reinforcing and even reinventing the process in the teaching-learning environment. There is no model to emulate but examples are numerous for Malaysia to review and adapt.